China's African FDI safari : opportunistic exploitation or muturally beneficial to all participants - Dreier, Tina,Rhodes University (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2013)
When implemented within a favourable legislative framework, Foreign Direct Investment (FDI) can produce domestic growth-enhancing spillovers in host countries. Other potential positive effects include the provision of investment capital, the creation of local employment and the transfer of sophisticated technology or advanced knowledge. African nations in particular have been historically reliant on externally-provided funds. Prevailing low income levels, marginal savings rates and the absence of functioning financial markets necessary to provide local start-up capital continue to keep Africa reliant on foreign inflows. Considering China's increasing financial commitments to Sub- Saharan Africa (SSA) over the last decade, this study examines the state of current Sino-African investment relationships. Specific attention is paid to the outcomes of this strategic bilateral alliance in order to determine whether or not a mutually beneficial investment relationship has evolved. The distinct nature and structure of, the motivation behind and the most significant determinants of Chinese FDI to SSA are all analysed in accordance with traditional FDI theories. A case study approach is used to establish whether China's contemporary interest in SSA differs from historical investments and to also investigate country-specific commonalities and differences. Of particular relevance to SSA are resource-backed Chinese loans that finance major infrastructure projects in host nations. Interestingly, a lot of the Sino-African investment packages resemble similar deals struck between China and Japan in the 1970s. The results of this study indicate that China's investment motives seem more diverse than initially expected. Resource-seeking, profit-seeking and market access-seeking reasons appear to be the most important motives. After establishing the Top- Ten recipients of Chinese FDI in SSA, these nations are then classified into three major categories: resource-, oil- or agricultural-rich nations. Undiversified resource- or oil-rich economies are found to have secured the largest shares of Chinese FDI. This study suggests that China's contemporary "African Safari" is an unconventional way of providing financial assistance. Rather than solely supplying FDI, China finances a diverse mix of instruments, the most important being concessional loans, export credits, zero-interest loans and the establishment of Special Economic Zones. A profound difference to traditional Western investment packages is China's non-interference approach. Accordingly, Beijing not only refrains from intervening in host countries' domestic affairs but also refuses to attach formal conditionalties to its loans. China's "financial safari" into Africa has produced many positive as well as negative effects in host countries. Nevertheless, it would seem that the positive effects outweigh the negative and China's FDI could contribute to sustainable development in SSA
Keywords: Africa -- Foreign economic relations -- China; China -- Foreign economic relations -- Africa; Investments, Foreign -- China; Foreign direct investment